Faktor-Faktor yang Mempengaruhi Kejadian BBLR di RSKD IA Pertiwi Makassar Tahun 2022 - Rahayu Rahayu; Rahmaniyah R (Pusat riset dan Inovasi Nasional, 2022)
Low birth weight (LBW) is defined by the World Health Organization (WHO) as a birth weight of less than 2,500 grams. LBW continues to be a significant public health issue globally and is associated with a range of short-term and long-term consequences. Overall, it is estimated that 15% to 20% of all births worldwide are low birth weight, representing more than 20 million births per year (WHO, 2014). The research aims to identify factors influencing the occurrence of LBW. This study adopts a simple observational design with a cross-sectional approach, a method that seeks to find factors related to independent variables (age, education, occupation, parity, pregnancy interval, gestational age) with the dependent variable of Low Birth Weight (LBW). The research findings at RSKD Mother and Child Pertiwi Makassar from 2022, reveal that, through the Chi-Square test, there are five variables that have no relationship with the occurrence of Low Birth Weight (LBW), namely age, education, occupation, parity, and pregnancy interval. There is only one variable, gestational age, that is associated with LBW. The study also highlights the characteristics of mothers delivering LBW babies at RSKD Mother and Child Pertiwi Makassar. Most of them are under the age of 20, accounting for 26 individuals (63.6%). The majority have basic education, with 26 individuals (50.0%), and the most common occupation is unemployed mothers, comprising 46 individuals (48.4%). Multiparous mothers are the highest in number, with 41 individuals (47.7%), and the majority have a pregnancy interval of less than 3 years, amounting to 28 individuals (54.8%). The gestational age is predominantly less than 37 weeks, with 31 individuals (100.0%). The study suggests the importance of recommending regular prenatal check-ups, a minimum of six times during pregnancy, for all normal or at-risk pregnant mothers.